Ethnographic collections from the Assiniboine and Yanktonai Sioux in the Field Museum of Natural History / Fieldiana, Anthropology, new series, no.26 - VanStone, James W.; Field Museum of Natural History. (Chicago, Ill. : Field Museum of Natural History, 1996)
The ethnographic collections of the Field Museum of Natural History contain 163 objects collected among the Assiniboine and Yanktonai Sioux by George Dorsey in 1900. Small collections were made for the World's Columbian Exposition by E. F. Wilson and Edward Ayer. The artifacts in these collections are described and illustrated. For comparative purposes, information is included from previous studies of the Assiniboine, Yanktonai, and neighboring peoples on the northern Plains. Includes bibliographical references (p. 26-27). The ethnographic collections of the Field Museum of Natural History contain 163 objects collected among the Assiniboine and Yanktonai Sioux by George Dorsey in 1900. Small collections were made for the World's Columbian Exposition by E. F. Wilson and Edward Ayer. The artifacts in these collections are described and illustrated. For comparative purposes, information is included from previous studies of the Assiniboine, Yanktonai, and neighboring peoples on the northern Plains. Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).